2017
DOI: 10.1177/1046878117750417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multitasking on Simulator Sickness and Performance in 3D Aerodrome Control Training

Abstract: Background. Air traffic controllers need to use their cognitive resources to cope with multiple tasks while monitoring air traffic. They are trained through advanced 3D simulators; however, they might demonstrate simulator sickness symptoms during this training. The relationship between multitasking and simulator sickness and the influence of different tasks on these variables can be investigated to inform further training practices for an efficient traffic monitoring. Purpose. The purpose of this quasi-exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Some participants both accepted their involvement in cyberloafing and resorted to their perceived multitasking advantage as a rationale; however, the empirical literature does not support this advantage (Kirschner & van Merrienböer, 2013). Multitasking may even interfere with the quality of instructional outcomes (Dindar & Akbulut, 2016;Fried, 2008;Sana, Weston, & Cepeda, 2013;Yoruk-Acikel, Turhan, & Akbulut, 2017). Contrary to empirical evidence, participants reported that they did not miss instructional activities for the sake of online technology use in class.…”
Section: Discussionmentioning
confidence: 91%
“…Some participants both accepted their involvement in cyberloafing and resorted to their perceived multitasking advantage as a rationale; however, the empirical literature does not support this advantage (Kirschner & van Merrienböer, 2013). Multitasking may even interfere with the quality of instructional outcomes (Dindar & Akbulut, 2016;Fried, 2008;Sana, Weston, & Cepeda, 2013;Yoruk-Acikel, Turhan, & Akbulut, 2017). Contrary to empirical evidence, participants reported that they did not miss instructional activities for the sake of online technology use in class.…”
Section: Discussionmentioning
confidence: 91%
“…Hava trafik kontrolörleri emniyet ve etkinlik açısından ortaya çıkan ya da çıkma potansiyeli olan problemleri çözme görevini yerine getirmektedirler. Bu görevin yeterliliği ve sürdürülebilirliği kontrolörlerin çoklu görev performansının başarısına bağlıdır [5]. Zihinsel, fiziksel ve davranışsal olarak ortaya koydukları ve koyacakları çalışma performanslarında temel, sürekli ve geliştirme eğitimleri hayati öneme sahiptir.…”
Section: Hava Trafik Kontrol Ve Acil Durum Yönetimiunclassified
“…An interaction between gender and topic sensitivity was also observed in terms of the extent of inconsistent responses. Male participants, for instance, tend to underreport physical problems in order not to appear weak (Yörük Açıkel et al, 2018), whereas female participants chose to underreport their behavior when the topic is socially sensitive (Akbulut et al, 2017;Dönmez & Akbulut, 2016).…”
Section: Introductionmentioning
confidence: 99%